Religiosity and health: A global comparative study. (April 2019) - Zimmer, Zachary; Rojo, Florencia; Ofstedal, Mary Beth; Chiu, Chi-Tsun; Saito, Yasuhiko; Jagger, Carol
Abstract: The objective of this paper is to understand global connections between indicators of religiosity and health and how these differ cross-nationally. Data are from World Values Surveys (93 countries, N=121, 770). Health is based on a self-assessed question about overall health. First, country-specific regressions are examined to determine the association separately in each country. Next, country-level variables and cross-level interactions are added to multilevel models to assess whether and how context affects health and religiosity slopes. Results indicate enormous variation in associations between religiosity and health across countries and religiosity indicators. Significant positive associations between all religiosity measures and health exist in only three countries (Georgia, South Africa, and USA); negative associations in only two (Slovenia and Tunisia). Macro-level variables explain some of this divergence. Greater participation in religious activity relates to better health in countries characterized as being religiously diverse. The importance in god and pondering life's meaning is more likely associated with better health in countries with low levels of the Human Development Index. Pondering life's meaning more likely associates with better health in countries that place more stringent restrictions on religious practice. Religiosity is less likely to be related to good health in communist and former communist countries of Asia and Eastern Europe. In conclusion, the association between religiosity and health is complex, being partly shaped by geopolitical and macro psychosocial contexts. Highlights: There is enormous global variation in how religiosity and health relate. Associations between religiosity and health differ across indicators of religiosity. An indicator of participation relates to good health in religiously diverse countries. Indicators related to belief and meaning of life relate to good health in poor countries with religious restrictions.